1999
DOI: 10.1002/(sici)1521-4141(199903)29:03<762::aid-immu762>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of the Leishmania antigen LACK by infected macrophages is dependent upon the virulence of the phagocytosed parasites

Abstract: We have previously demonstrated that murine macrophages (Mphi) infected with Leishmania promastigotes, in contrast to Mphi infected with the amastigote stage of these parasites, are able to present the Leishmania antigen LACK (Leishmania homologue of receptors for activated C kinase) to specific, I-Ad-restricted T cell hybrids and to the T cell clone 9.1-2. These T cells react with the LACK (158-173) peptide, which is immunodominant in BALB/c mice. Here, we show that the level of stimulation of the LACK-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 23 publications
(40 reference statements)
2
53
0
1
Order By: Relevance
“…Studies on presentation of the Leishmania antigen, Leishmania homolog of receptors for activated C kinase (LACK), by infected macrophages showed a transient yet strong LACK-specific T cell response when infected with stationary or log phase Leishmania promastigotes. On the other hand, murine macrophages infected with either Leishmania metacyclic promastigotes or amastigotes showed a weak or absent LACK-specific T cell activation respectively (Courret et al, 1999). Membrane lipid rafts are important platforms for antigen presentation as it concentrates MHC class II molecules into microdomains, which allow efficient antigen presentation at low peptide densities.…”
Section: Mechanisms Of Immune Evasionmentioning
confidence: 99%
“…Studies on presentation of the Leishmania antigen, Leishmania homolog of receptors for activated C kinase (LACK), by infected macrophages showed a transient yet strong LACK-specific T cell response when infected with stationary or log phase Leishmania promastigotes. On the other hand, murine macrophages infected with either Leishmania metacyclic promastigotes or amastigotes showed a weak or absent LACK-specific T cell activation respectively (Courret et al, 1999). Membrane lipid rafts are important platforms for antigen presentation as it concentrates MHC class II molecules into microdomains, which allow efficient antigen presentation at low peptide densities.…”
Section: Mechanisms Of Immune Evasionmentioning
confidence: 99%
“…The culture conditions have been described previously (20). Metacyclic promastigotes were isolated by negative selection with peanut agglutinin (Vector Laboratories, Burlingame, CA) as previously described (21).…”
Section: Parasitesmentioning
confidence: 99%
“…L. amazonensis replicates in the gut of flies of the genus Lutzomia and there it differentiates into a metacyclic, infective parasite (Lainson et al 1987). Infective parasites express different carbohydrates on their surface than do non-infective forms (Saraiva et al 1986, Courret et al 1999. Parasites reach the vertebrate host when the fly feeds on the host's blood and regurgitates parasites present in the mouth or adjacent posterior regions (Killick-Kendrick 1990).…”
mentioning
confidence: 99%
“…Once in the vertebrate host, Leishmania metacyclic promastigotes interact with macrophages through ligand receptor-mediated residues on their surfaces and mannose receptors on the macrophage surface (Mosser et al 1987, Da Silva et al 1989. Metacyclic promastigotes interact with macrophages differently than non-infective forms (Courret et al 1999, Saraiva et al 2005 and they have been shown to impair the capacity of macrophages to present antigens (Courret et al 1999). However, most studies use stationary phase cultures, which contain mostly (80%) non-infective forms, for experimental infections (Scott 1989, da Costa et al 1992, Afonso & Scott 1993, Santiago et al 1999, Ji et al 2003.…”
mentioning
confidence: 99%
See 1 more Smart Citation